Professional guide to assessment. (Professional Guide Series., 2006)
Continuing the tradition of comprehensive coverage found in other titles of the Professional Guide Series, Professional Guide to Assessment provides in-depth, detailed, essential how-to information about patient assessment for all health professionals. This complete, yet concise reference uses a structured, organized approach to assessment, highlighting basic as well as more advanced techniques in an easy-to-use, highly visual format appropriate for any health care professional, regardless of the practice setting. An 8-page full-color insert highlights cardiac and respiratory assessment techni.